Effect of photoperiod on the life cycle of Diatraea saccharalis - Parra, J. R. P.; Melo, A. B. P.; Magalhães, B. P.; Neto, S. Silveira; Botelho, P. S. M. (Pesquisa Agropecuaria Brasileira, 2014)
This work was carried out in the laboratories of the Department of Entomology of ESALQ - USP, State of São Paulo, Brazil, with photoperiod equipment developed there. This research was divided into two phases: the first under e low temperature condition (mean of 23.3ºC) and the second in a high temperature room (mean of 26.4ºC). The following treatments were studied (photophase: scotophase): 0:24; 6:18; 12:12; 14:10; 18:6 and 24:0. Diatraea saccharalis (F., 1794) (two larvae/container) were maintained inside glass containers with artificial diet, in a total of 100 per treatment. There was an interaction between photoperiod and temperature, mainly at the lower temperatures. Therefore, in the first phase of the experiment, it was observed that the shortest larval period occurred in the 24 hour photophase treatment; but in the second phase the shortest larval period occured in the 12:12 treatment. In both situations, the light pupae and the great percentage of adult malformations were obtained in the 24 hour photophase treatment, with the 0:24 and 12:12 photoperiodic conditions presenting the highest pupae weights. On the other hand, the shortest adult malformation percentage was observed as the 18:6 and 12:12 treatments, in both phases of the research.